Perubahan Perilaku pada Pelaku Pernikahan Usia Dini (di Desa Padang Capo Kab. Seluma Prov. Bengkulu) - Ririn Shepta Deanty; Linda Safitra; Ayu Wijayanti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the behavioral changes experienced by perpetrators of early marriage in Padang Capo Village, Seluma Regency, Bengkulu Province. Early marriage is still a pressing problem, especially in rural areas, despite various counseling efforts and government policies. This practice is generally influenced by low socioeconomic conditions, local cultural norms, limited education, and pregnancy before marriage. This study used a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. To understand the behavioral changes that occur, this study uses behavioral theory in sociology, which emphasizes that individual behavior is formed through the process of social learning, reinforcement from the environment, and adaptation to new social norms and roles.The main subjects in this study are four individuals who married under the age of 18. The results showed that early marriage resulted in complex and multidimensional behavioral changes, including emotional, psychological, social, and family aspects. Some informants experienced high emotional stress, limited access to education, and loss of personal freedom, especially after giving birth. However, some also showed signs of adaptation and emotional growth in their marital relationships. Changes in the social environment and new responsibilities contributed to.